130k views
3 votes
HALP MEEEEEEEEEEEEEEE

HALP MEEEEEEEEEEEEEEE-example-1
User LucG
by
4.8k points

2 Answers

0 votes
  • a_1=-1

a_2

  • -3a_1+6
  • -3(-1)+6
  • 9

a_3

  • -3(9)+6
  • -21

a_4

  • -3(-21)+6
  • 69
User Akolade Adesanmi
by
4.4k points
5 votes

Answer:

  • -1, 9, - 21, 69

Explanation:

Given recursive formula:

  • a₁ = -1
  • aₙ = - 3aₙ₋₁ + 6 for n ≥ 2

The first 4 terms are:

  • a₁ = - 1, given
  • a₂ = - 3*(-1) + 6 = 3 + 6 = 9
  • a₃ = - 3*(9) + 6 = - 27 + 6 = - 21
  • a₄ = - 3*(-21) + 6 = 63 + 6 = 69
User Ankit Soni
by
4.9k points